1990
DOI: 10.1103/physrevlett.64.507
|View full text |Cite
|
Sign up to set email alerts
|

Interference between optical transitions

Abstract: We report observations of an interference between optical transition amplitudes for linear and nonlinear excitation of the mercury 65 ] So-* 6p ] P\ transition. The transition probability is varied sinusoidally by changing the relative phase of the two fields inducing these distinct processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
163
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 322 publications
(166 citation statements)
references
References 24 publications
(3 reference statements)
2
163
0
1
Order By: Relevance
“…This control scenario is an extension of Elliott's twocolor photoionization experiments on alkali atoms [14,15,32,33], which demonstrated that the angular distribution of an emitted photoelectron can be controlled by the relative phase between two ionizing laser beams. The sensitivity to phase was attributed to quantum interference between competing ionization processes.…”
Section: Application To Photoelectron Spin Polarization Control In Almentioning
confidence: 99%
See 2 more Smart Citations
“…This control scenario is an extension of Elliott's twocolor photoionization experiments on alkali atoms [14,15,32,33], which demonstrated that the angular distribution of an emitted photoelectron can be controlled by the relative phase between two ionizing laser beams. The sensitivity to phase was attributed to quantum interference between competing ionization processes.…”
Section: Application To Photoelectron Spin Polarization Control In Almentioning
confidence: 99%
“…For example, the path alternatives are given by the two excitation processes in a 1 vs. N coherent control scenario. The resultant CCI framework is general and applicable to many systems, from atoms [15,66] to molecules [27,45,[67][68][69] to bulk solids [4,5,20,30,[70][71][72][73][74][75]. Further, the control field can be in a semiclassical coherent or in a quantum state of light, such as a multimode Fock state or a squeezed state.…”
Section: A General Overview Of This Articlementioning
confidence: 99%
See 1 more Smart Citation
“…It was first experimentally realized in 1989 on atoms and later also in small to medium-sized molecules [11][12][13][14]. In the model system depicted in Fig.…”
Section: Single-parameter Controlmentioning
confidence: 99%
“…This spectral shift is often subtracted from the phase φ (t): 11) introducing the time dependent phase ϕ(t). With this relation, the momentary frequency ω(t), which is defined as the time-derivative of the temporal phase φ (t) can be written as:…”
Section: Mathematical Description Of Femtosecond Laser Pulsesmentioning
confidence: 99%